Dysbiosis Contributes to Arthritis Development via Activation of Autoreactive T Cells in the Intestine. Issue 11 (27th October 2016) - Maeda, Yuichi; Kurakawa, Takashi; Umemoto, Eiji; Motooka, Daisuke; Ito, Yoshinaga; Gotoh, Kazuyoshi; Hirota, Keiji; Matsushita, Masato; Furuta, Yoki; Narazaki, Masashi; Sakaguchi, Noriko; Kayama, Hisako; et al.
Abstract : Objective: The intestinal microbiota is involved in the pathogenesis of arthritis. Altered microbiota composition has been demonstrated in patients with rheumatoid arthritis (RA). However, it remains unclear how dysbiosis contributes to the development of arthritis. The aim of this study was to investigate whether altered composition of human intestinal microbiota in RA patients contributes to the development of arthritis. Methods: We analyzed the fecal microbiota of patients with early RA and healthy controls, using 16S ribosomal RNA−based deep sequencing. We inoculated fecal samples from RA patients and healthy controls into germ‐free arthritis‐prone SKG mice and evaluated the immune responses. We also analyzed whether the lymphocytes of SKG mice harboring microbiota from RA patients react with the arthritis‐related autoantigen 60S ribosomal protein L23a (RPL23A). Results: A subpopulation of patients with early RA harbored intestinal microbiota dominated by Prevotella copri ; SKG mice harboring microbiota from RA patients had an increased number of intestinal Th17 cells and developed severe arthritis when treated with zymosan. Lymphocytes in regional lymph nodes and the colon, but not the spleen, of these mice showed enhanced interleukin‐17 (IL‐17) responses to RPL23A. Naive SKG mouse T cells cocultured with P copri −stimulated dendritic cells produced IL‐17 in response to RPL23A and rapidly induced arthritis. Conclusion: We demonstrated that dysbiosis increases sensitivity to arthritis via activation of autoreactive T cells in the intestine. Autoreactive SKG mouse T cells are activated by dysbiotic microbiota in the intestine, causing joint inflammation. Dysbiosis is an environmental factor that triggers arthritis development in genetically susceptible mice.